Proceedings of the 2015 ACM SIGCHI Conference on Creativity and Cognition 2015
DOI: 10.1145/2757226.2757248
|View full text |Cite
|
Sign up to set email alerts
|

Building Support Tools to Connect Novice Designers with Professional Coaches

Abstract: Creativity support tools help learners undertake creative work, such as facilitating coaching by creative professionals. How might we design creativity support tools that increase learners' access to coaching by creative professionals? This study took place in an extracurricular projectbased learning program where students were co-located, and met professional coaches face-to-face once a week but otherwise communicated online. To test an online creativity support tool called the Loft and investigate coach-stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Unfortunately, there are barriers to volunteer professionals coaching in PBL. In a previous study in the same program (previous year) as the current study, in we identified barriers for volunteer professional design coaches maintaining engagement outside of face‐to‐face meetings (Rees Lewis et al ., ). As a result, although coaches agreed to support teams with both weekly face‐to‐face meetings and online between meetings, no significant coaching occurred online.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Unfortunately, there are barriers to volunteer professionals coaching in PBL. In a previous study in the same program (previous year) as the current study, in we identified barriers for volunteer professional design coaches maintaining engagement outside of face‐to‐face meetings (Rees Lewis et al ., ). As a result, although coaches agreed to support teams with both weekly face‐to‐face meetings and online between meetings, no significant coaching occurred online.…”
Section: Introductionmentioning
confidence: 97%
“…Volunteer professionals might play a range of design coaching roles in PBL as they work with teams, such as modeling more challenging tasks, diagnosing student struggles and prompting students to reflect. However, volunteer professionals, who predominantly work in industry, can only periodically meet face‐to‐face and so experience significant barriers to staying involved in design coaching students (Rees Lewis, Harburg, Gerber, & Easterday, ): students both do not spontaneously update coaches about their project as it takes time to communicate, diminishes self‐esteem and they may not view time spent communicating as valuable. Furthermore, volunteer professional coaches may not proactively prompt students for information (as a teacher might).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations